IMPLEMENTATION OF CORPORATE SOCIAL INITIATIVE AT WAROENG STEAK AND SHAKE OUTLET GATOT SUBROTO, BANDAR LAMPUNG: PENERAPAN CORPORATE SOCIAL INITIATIVE PADA OUTLET WAROENG STEAK AND SHAKE GATOT SUBROTO, BANDAR LAMPUNG - Firdaus, Ridho Iqbal; Damayanti, Damayanti; Subagja, Ghia (Jurnal Kompetitif Bisnis, 2023)
A company in running a business has various strategies to support the achievement of company goals. In corporate practice, implementing the main program that is intended for internal companies and external communities is a derivative of the concept of corporate social responsibility which we know as the Corporate Social Initiative. This research is a descriptive qualitative research that aims to determine the implementation of the Corporate Social Initiative at Waroeng Steak And Shake Outlets. The purpose of this study was to determine the implementation of the Corporate Social Initiative and the constraints faced at the Waroeng Steak And Shake Outlet Gatot Subroto, Bandar Lampung. The results of this study are (1) changes in the ability of employees in discipline and on time in carrying out work; (2) building a positive image of the Waroeng Steak And Shake brand; (3) build a good working environment for the company's internal.